1992
DOI: 10.1111/j.1540-6261.1992.tb04679.x
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Illegal Insider Trading

Abstract: Whether insider trading affects stock prices is central to both the current debate over whether insider trading is harmful or pervasive, and to the broader public policy issue of how best to regulate securities markets. Using previously unexplored data on illegal insider trading from the Securities and Exchange Commission, this paper finds that the stock market detects the possibility of informed trading and impounds this information into the stock price. Specifically, the abnormal return on an insider trading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
376
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 636 publications
(403 citation statements)
references
References 17 publications
20
376
2
5
Order By: Relevance
“…A detailed analysis of available news releases from the period under study does not bring any excuses for observed abnormal returns and volumes. Meulbroek (1992) as well as Cornell and Sirri (1992) show that such unexplained alerts appear on days marked by insider trading. Although they cannot pose any kind of statistical proof of market abuse behavior, they give an important signal for the financial supervisory authority that should closely monitors markings of the companies.…”
Section: The Analysis Of Abnormal Trading Volumesmentioning
confidence: 91%
See 1 more Smart Citation
“…A detailed analysis of available news releases from the period under study does not bring any excuses for observed abnormal returns and volumes. Meulbroek (1992) as well as Cornell and Sirri (1992) show that such unexplained alerts appear on days marked by insider trading. Although they cannot pose any kind of statistical proof of market abuse behavior, they give an important signal for the financial supervisory authority that should closely monitors markings of the companies.…”
Section: The Analysis Of Abnormal Trading Volumesmentioning
confidence: 91%
“…Increased trading volume may be noted simultaneously. Meulbroek (1992) states that this can be caused by uninformed investors who follow insiders and empower the changes in trading. The so-called herd-effect on the Polish stock market is studied by Gurgul and Majdosz (2007).…”
Section: Introductionmentioning
confidence: 99%
“…The SEA of 1934 and the amendment provisions from the Williams Act of 1966 were aimed at curtailing illegal insider trading and protecting minority shareholders against losses that they might incur while trading against informed insiders. These regulatory provisions state that any person who is in possession of material, non-public information is not allowed to trade, and any violation amounts to a criminal infraction [27]. Sections 10 and 14 both state that any person who is in possession of material, non-public information should abstain from trading or from disclosing such information.…”
Section: Regulatory Frameworkmentioning
confidence: 99%
“…Not all insider trading is illegal, and offences are not always easily detectable. Meulbroek (1992), in a study of 183 cases listed by the SEC, shows that the abnormal price movement on an illegal insider trading day is 40 to 50% of the subsequent price reaction to the public announcement of the inside information. 2 See Bhattacharya and Daouk (2004), who argue for insider trading that it is sometimes better not to have a law than to have a law but not enforce it.…”
Section: Characteristics Of Repurchasing Firmsmentioning
confidence: 99%